Paciente femenina de 58 años de edad con hipotiroidismo y obesidad grado I - Torres Bajaña, Indira Selene (2018)
The case study is related to a patient's 58-year-old native of the parish La Unión, married and with a daughter, was diagnosed with hypothyroidism 4 years ago, hypothyroidism takes daily medication for hypothyroidism, according to the WHO in 2009 It has a rate of 5 to 15 percent of the world's population, the risk increases with age. When the evaluation anthropometric as BMI was detected that the patient is in obesity grade I with moderate cardiovascular risk. According to the anamnesis made the patient maintains unhealthy eating habits, their biochemical tests are within normal values. Nutrition education in when to the importance of maintaining healthy eating habits in order to avoid the complications of hypothyroidism, in addition he intervened with a nutrition plan with a diet of 1854 kcal/day low in saturated fat, with 25 g of fiber/day divided into 5 meals a day, according to the energy requirement of the patient, In addition, the weight loss of 2.5 kg per month was evidenced, according to the monitoring which was carried out for 6 months